2022
DOI: 10.24095/hpcdp.42.9.03
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of perceived success of health-promoting interventions in elementary schools

Abstract: Introduction School-based health-promoting interventions (HPIs) aim to support youth development and positively influence modifiable lifestyle behaviours. Identifying factors that contribute to or hinder the perceived success of HPIs could facilitate their adaptation, improve implementation and contribute to HPI sustainability. The objective of this study was to identify factors in three domains (school characteristics, characteristics of the HPI and factors related to planning and implementing the HPI) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…We noted that school physical environment and ease of principal leadership, which have been associated with health promotion effectiveness in other studies, 36,46,47 did not vary by school deprivation in PromeSS. If confirmed, this has positive implications for school health promotion across schools.…”
Section: Implications For School Health Policy Practice and Equitysupporting
confidence: 52%
See 3 more Smart Citations
“…We noted that school physical environment and ease of principal leadership, which have been associated with health promotion effectiveness in other studies, 36,46,47 did not vary by school deprivation in PromeSS. If confirmed, this has positive implications for school health promotion across schools.…”
Section: Implications For School Health Policy Practice and Equitysupporting
confidence: 52%
“…There was, however, a gradient by social deprivation in this scale. Although not detectable at the 0.05 level, this finding could be important given that other studies have identified staff commitment and school prioritization of health as key factors for health promotion effectiveness 36,46,47 . Factors that might explain why commitment is lower in more deprived schools include staff facing urgent social and educational needs which take precedence over health needs, and staff having lower confidence that any intervention will make a difference for students.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Data collection procedures are detailed elsewhere. 13 , 16 Briefly, data were collected in a two-part, structured telephone interview (median length = 52 min) administered by trained interviewers in French or English. School principals were solicited; if they had not worked in their current school at least six months or were unavailable, they were asked to nominate another key informant (i.e.…”
Section: Methodsmentioning
confidence: 99%